The anarchy and the feminism in Spain: the anarchistic offers of freedom to women for obtaining the equality of genders (Foro de Educacion, 2024)
In the first decades of the 20th century, the women started organizing with the purpose of having a more active role in the society. They obtained the incorporation to the political life during the arrival of the Second Republic, but they conti- nued being discriminated. In the anarchists’ case, some women of the Workers Organizations decided to create her own organization called Free Women. The main reasons of that organization were claim her rights, and to liberate the woman from their slave’ situation of ignorance, of the work and, of her sexual condition. When the Spanish Civil war exploded, Free Women not only fought against the fascism, but also against the own anarchists, who thought that the woman was the man’s slave. The education and the vocational training will be the main tools that they used to qualify the women and to try to reach their emancipation.